Key drivers of income diversification among smallholder sweet potato farmers in Greater Tzaneen Municipality - Mokhaukhau, Jenny Potsiso; Matlala, Florence; Matlala, Lesetja Jacob; Thaba, Tshepi Kingsley (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
This study examines the key factors influencing income diversification among smallholder sweet potato farmers in Greater Tzaneen Local Municipality, South Africa. Income diversification is crucial for improving farmers' livelihoods and reducing economic vulnerability. A purposive sampling method identified 109 smallholder farmers, and data collection was conducted using semi-structured questionnaires. Descriptive statistics provided insights into farmers' demographic characteristics, while a binary logistic regression model assessed the impact of various socio-economic factors on income diversification. The results reveal that the average age of farmers is 43 years, with nine years of farming experience on average. The regression analysis indicates that age, distance to market, and education level significantly influence farmers' likelihood of diversifying their income sources. Younger farmers are more inclined towards diversification, while those farther from markets are more likely to seek alternative income opportunities. The findings suggest that providing targeted training and enhancing access to non-farm income opportunities can promote income diversification, particularly for younger farmers. This study contributes to understanding how socio-economic factors shape income diversification decisions, offering insights for policymakers aiming to support smallholder farmers' economic resilience.